MANAGING QUALITY IN THE NON-FORMAL SECONDARY EDUCATION SECTOR: A CASE STUDY OF INDEPENDENT COLLEGES, MIDLANDS PROVINCE, ZIMBABWE - Mudzimba, Edward; Chokera, Fainos; Ngwenya, Tendai (British Journal of Marketing Studies, 2014)
The study is an evaluation of the quality of education offered by small independent colleges in Zimbabwe. Focus was on (1) the level of compliance of independent colleges to the government requirements on quality education (2) perceptions held by students on the quality of education they experience in the independent colleges and (3) challenges faced by independent colleges in providing quality education. Data was collected from the 320 respondents being students, staff of the independent colleges and representatives from the ministry of education and culture and the Zimbabwe Council for Education (ZIMSEC). The main instruments of the study are questionnaires and interviews. The study found out that Independent colleges are failing to meet governments requirements on quality education and their students have negative perceptions towards the quality of education they are receiving. Lack of funding emerged as the main challenge affecting independent colleges in providing quality education. The study recommends the government to strengthen its monitoring and supervisory efforts in the non-formal education sector. Independent colleges are also urged to seek strategic partnerships with other players locally or internationally to reduce their financial burden.